(untitled) (International Journal of Innovative Technologies in Economy, 2021)
Tourism is one of the most important fields of the world economy. In recent years, world tourism has been a direction of special priority and the attention to it has increased considerably. The importance of tourism to the World Heritage was gradually increasing, which changed both opportunities and danger. The World Heritage Center was tasked with developing a solid World Heritage Tourism Development Program. The purpose of this program is to help the World Heritage Committee and the management of the facilities use tourism as a positive factor in preserving the world heritage and mitigating the expected threats. Although there are suitable environmental conditions for the development of tourism in the world, it is significantly affected by such risks as: climate, natural disasters, political situation, various viruses, pandemics, etc. This kind of risk that fundamentally changed tourism around the world today is COVID-19, to which our article is dedicated.